Prosecution in a Pre-Trial Investigation Requires Fundamental Renewal - Popovych, I. M. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article is devoted to the analysis of the current state of the prosecution in the domestic pre-trial investigation. Investigating the problematics, the author focuses his attention on certain gaps and miscalculations of the current legislation in determining the party of the prosecution. The author's vision of ways to eliminate these mistakes and improve the functioning of the prosecution in the criminal proceedings of Ukraine is proposed.